ҚАРАҚАЛПАҚ ТИЛИ ФРАЗЕОЛОГИЯСЫНЫҢ КӨЛЕМИ ҲӘМ ШЕГАРАСЫ - Пирниязова, А.Қ. (FAN va JAMIYAT, 2019)
The article deals with capacity and treaties of phraseological units in Karakalpak. It was given some hypothesis on this issue. The author gives a review of investigations in phraseology of the Russian and Turkic languages.